Pengaruh Earning Per Share dan Economic Value Added terhadap Return Saham pada Perusahaan yang Terdaftar di Jakarta Islamic Index - Imroatin, Choirul; Widhianningrum, Purweni (Universitas Muhammadiyah Malang)
This study aimed to analyze the influence Earning Per Share and Economic Value Added on stock returns. This study is a quantitative research. The population in this study is a company registered in the group of Jakarta Islamic Index period in 2011, 2012, 2013, and 2014. The sampling technique used purposive sampling, so the final number of samples acquired 11 companies. The data analysis used is multiple linear regression. The results proved that Earning Per Share and Economic Value Added have a significant effect on stock returns in Jakarta Islamic Index period in 2011, 2012, 2013, and 2014. Keywords: Earning Per Share, Economic Value Added, Return, Jakarta Islamic Index.